Impact of stressors in the aviation environment on xenobiotic dosimetry in humans: physiologically based prediction of the effect of barometric pressure or altitude. Issue 8 (17th April 2020) - Sweeney, Lisa M.
ABSTRACT: Standard health risks from volatile organic compounds (VOCs) are generally interpreted at ambient environmental conditions. The aim of this study was to develop a strategy for using physiologically based pharmacokinetic (PBPK) modeling to compare known risks in the general population to calculated risks in pilots experiencing pressure-based stressors. PBPK models facilitate these comparisons by prediction of how target-tissue specific doses are altered when a stressor, such as high altitude, produces changes in physiological parameters. Cardiac output, regional blood flow, and alveolar ventilation rate following acute exposure to altitude ranging from moderate to extremely high were estimated from published data from 52 groups of human subjects. Scenarios where pilots might inhale toluene, 1, 2, 4-trimethylbenzene (1, 2, 4-TMB), or cyclohexane during routine military flight training were simulated. At the recommended Threshold Limit Values (TLV), arterial blood concentrations were predicted to be higher for exposure at 15000 ft (4572 m) than at sea level. The differences were greater for toluene and TMB, which have higher blood: air and fat: blood partition coefficients than less lipophilic cyclohexane. In summary, quantitative approaches to internal dosimetry prediction that take advantage of existing knowledge of physiological changes induced by occupational stressors possess potential as tools in performing a human health risk assessment.